Sustainable Urban Development and Office Location - Zięba, Małgorzata (Journal of Public Governance, 2021)
The paper explores the criteria of selecting a location for new office projects by developers and analyses them in relation to the principles of sustainable urban development. Real estate market participants should be part of the sustainable urban development process, due to the impact of the built environment on cities’ functioning. Thus, the overall research question has been if there is an intersection between social needs for urban sustainability and commercial goals of office developers. The paper discusses results of qualitative research (semi-structured interviews) among office developers in Cracow. The focus of the research has been narrowed down to the selected aspects of the complex relations between the real estate market and urban development, i.e., the location of office buildings.The developers emphasized access to well-developed public transportation networks, access to urban amenities and services as crucial features of good location, attractive for end-users. Thus, the attractive location of office building, is consistent with principles of sustainable urban development. Research findings emphasize significance of market participants’ awareness of urban sustainability concept, as this leads them to exert pressure on developers to create more sustainable buildings and choose more adequate locations. Furthermore, local sustainable urban development strategy and policies, create framework for developers to make more sustainable choices of location. Original contribution to knowledge on dynamically growing office market in Cracow, by revealing office location preferences of developers as well by confronting these preferences with urban sustainability requirements. It broadens the analysis of office location preferences by adding context of urban sustainability. Due to the significance of findings for urban development, the research opens opportunities for further analysis on more comprehensive sample.